Echoes of despair: the haunting legacy of Gloomy Sunday: Hungarian suicide song, its psychological impact on university students, and implications for the educational learning environment and state response - Abdul Hisam, Siti Nasyrah; Shariffuddin, Norashikin (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The song Gloomy Sunday (Szomorú Vasárnap), composed in 1933 by Hungarian pianist Rezső Seress, is known for its deeply melancholic tone and controversial association with alleged suicide cases. Written during a time of personal hardship and national crisis in Hungary following World War I and the Treaty of Trianon, the song later refined with lyrics by László Jávor explores themes of grief, lost love, and profound despair.